CLASSIFICATION OF EXPERT OPINIONS AND THEIR EVIDENTIARY VALUE IN ADMINISTRATIVE PROCEEDINGS - Yudina, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to analyze the classification of the expert’s opinions and to find out their evidentiary value in administrative proceedings. Research methods: the dialectical method of cognition was applied, with the help of which a general theoretical study of the classification of expert opinions was carried out, a comparative-legal method for the analysis of the approaches of scientists to the evidentiary value of probable opinions and opinions about the impossibility of solving the issue, comparative-legal and formal-legal methods for the analysis of legislation, as well as methods of systematization and generalization. Results: the grounds for the classification of the expert’s opinions were analyzed. The author distinguished between the legal nature of the opinion on the impossibility of solving the issue and the report on the impossibility of conducting a forensic examination, as well as proposed an additional basis for the classification of expert opinions by subject composition, according to which expert opinions are divided into individual expert opinions and collegial expert opinions. However, the expert’s individual opinion, in the opinion of the author, can also be complex, provided that within the framework of one forensic examination, multidisciplinary expert studies are conducted by one expert in related expert specialties, such as technical examination of documents and handwriting examination. The specified position corresponds to the realities of modern expert practice, but it will be possible to fully accept it only after legislative consolidation. Discussion: the expert’s categorical opinions s have unconditional evidentiary value, and the expert’s probable opinions can be considered as full-fledged evidence only in combination with other evidence in the administrative case, provided that such opinions do not contradict other evidence.